Conocimiento y práctica del cuidado domiciliario del recien nacidos en madres adolescentes del establecimiento de salud Morona Cocha Iquitos 2023 - Ramírez Sánchez, Lucila Pilar (2024)
The objective was to determine the relationship between the knowledge and practice of home care of the Newborn, in mothers aged 14 to 19 years, cared for at the E.S. Morona Cocha, Iquitos 2023. It is a quantitative, non experimental, descriptive, cross-sectional and correlational study; The population was made up of 30 adolescent mothers. The techniques used were: the survey and home visit, instruments: questionnaire on knowledge of home care and questionnaire on practice on home care of the R.N. (validity 97.50% and 96.25%) and (reliability 81.0% and 80.0%). The results obtained were: 53.3% presented medium, 26.7% high and 20.0% low knowledge about the home care of the National Nur. Regarding the practice of home care of the National Nur, 56.7% of mothers presented adequate practice and 43.3% inadequate practice. When relating knowledge with home care practice of the National Reserve, a significant correlation was obtained (Rho = 0., 435; p = 0.016 < 0.05), between the dimensions hygiene (Rho = 0.389; p = 0.034 < 0.05) and warning signs (Rho = 0.388: p = 0.033 < 0.05); there was no significance in diet (Rho = 0.061; p = 0.751 > 0.05), thermoregulation (Rho = 0.091; p = 0.633 > 0.05), sleep (Rho = 0.079; p = 0.679 > 0.05), clothing (Rho = 0.024; p = 0.899 > 0.05) and elimination (Rho = 0.211; p = 0.264 > 0.05) with home care practices. Concluding that, the greater the medium/high knowledge of home care, the more adequate maternal care practices are obtained in adolescents.